ОТДАЛЕННАЯ ПОСЛЕОПЕРАЦИОННАЯ КОГНИТИВНАЯ ДИСФУНКЦИЯ - Дубовская С. С.; Товажнянская Е. Л.; Григоров Ю. Б.; Кудинова О. В.; Соловйова Е. Т. (World Science, 2018)
Postoperative cognitive dysfunction develops in the early and persists in the late postoperative period. Clinically, this condition manifests itself in the form of memory impairment, violation of concentration and violation of other higher functions of the cerebral cortex. The aim of this study is to study cognitive function in patients who underwent surgery with the use of general anesthesia in a remote period in a month. According to the results of the MMSE test, in the middle-aged patients the dynamics of the deterioration of the cognitive function was observed to a lesser degree than in the young patients, which is probably related to the age-related features of the plasticity of the cognitive function. In patients of middle age, according to the results of the FAB scale, at this period of the study was at the same level as those in young patients, which is associated with the age specificity of the plasticity of the cognitive function. According to the test drawing hours, there was no significant difference in the recovery rate, it was gradual, but no complete restoration was observed. For the 10-word memory test and the Schulte trial, the recovery was gradual, with a full recovery of the indicator to the level before the operation.